Ensure Results of Queries to Service Provider’s Databases - Pham, Thi Bach Hue; Dang, Tran Khanh (Journal of Technical Education Science, 2009)
With rapid advances in networking technologies and big demand for data management, outsourcing database services has recently been a new trend. In this outsourcing model, a service provider is typically not fully trusted, and thus they raise numerous problems related to security issues. These problems are referred to as data confidentiality, user privacy, data privacy, and query assurance. Among them, query assurance takes an important role to the success of the database outsourcing model. In this paper, we present existing solutions to query assurance for outsourced databases, both traditional databases and XML databases. Besides, we discuss and evaluate all of them and propose future research directions related.